Use of waste of metallurgical and hydrogen industry in the production of binding substances - Shyshkina , O.O.; Shyshkin, O.O. (Ways to Improve Construction Efficiency, 2022)
The current state of construction science development dictates the use of high–strength binders and concrete based on them during the construction of unique buildings and structures, as well as the construction of complex constructions and their repair.Currently, two main directions in the use of mineral raw materials have been clearly defined. The first direction consists in increasing the degree of use of natural resources at existing and new enterprises. The second is in the creation of zero–waste and low–waste productions associated with technologies aimed at maximum utilization of waste. Thus, multi–tonnage waste of metallurgical enterprises – domain slag – found wide application, first of all, in the building materials industry. The effect of the interaction between sodium silicates and iron compounds and the resulting so–called slag binder, which is a mixture of granulated blast furnace slag with waste from mining and beneficiation plants (iron–containing mineral complex), closed with water, was established.These two provisions served as the basis for obtaining a new type of binder, the so–called alkaline slag slurry, which is a mixture of granulated blast furnace slag with an iron–containing mineral complex. At the same time, iron ore beneficiation waste is used as an iron–containing mineral complex. The specified mixture, when mixed with an aqueous solution of an alkaline component, in the presence of a hydrophobic surface–active substance hardens with the formation of an artificial stone, which has a compressive strength of up to 160 MPa. In a model experiment, the influence of the composition of the composite, which is a mixture of industrial production waste: granulated blast furnace slag and iron ore beneficiation waste, on the strength of the stone obtained as a result of the hardening of this composite when mixing it with an aqueous solution of an alkaline component in the presence of a hydrophobic surfactant was studied.